The effect of a very low-calorie diet (VLCD) with and without concomitant resistance exercise training (RET) or high-intensity interval training (HIIT) on body composition, muscle function and metabolism - Abdul Aziz, Muhammad Hariz (2021)
Background: Weight loss is beneficial for health in many aspects, including reducing the risk of various diseases such as type 2 diabetes mellitus, cardiovascular disease, respiratory problems and many more. A very low-calorie diet is one of the methods that can provide rapid weight loss. Unfortunately, there are concerns regards to muscle and lean mass loss with the weight loss process. Exercises particularly resistant exercise training (RET) is known to stimulate muscle growth; however, research combining RET with VLCD is scarce. High-intensity interval training (HIIT) has recently emerged as an ‘efficient’ exercise that can fit many busy lifestyles. However, no study has been done to combine HIIT with VLCD to compare its benefit with diet only or with RET.